2022
DOI: 10.1021/jacs.2c01669
|View full text |Cite
|
Sign up to set email alerts
|

Resonance-Induced Stimuli-Responsive Capacity Modulation of Organic Ultralong Room Temperature Phosphorescence

Abstract: Organic ultralong room temperature phosphorescence (OURTP) materials having stimuli-responsive attributes have attracted great attention due to their great potential in a wide variety of advanced applications. It is of fundamental importance but challengeable to develop stimuli-responsive OURTP materials, especially such materials with modulated optoelectronic properties in a controlled manner probably due to the lack of an authentic construction approach. Here, we propose an effective strategy for OURTP mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 64 publications
0
57
0
Order By: Relevance
“…The most common approach to obtaining MSR properties is to construct π‐conjugated donor–acceptor (D‐π‐A) molecular structures with through‐bond charge transfer (TBCT) properties [8, 16, 22–26] . The π‐conjugated molecular structure enables molecules to have different molecular packing modes in different aggregation states [16, 24] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common approach to obtaining MSR properties is to construct π‐conjugated donor–acceptor (D‐π‐A) molecular structures with through‐bond charge transfer (TBCT) properties [8, 16, 22–26] . The π‐conjugated molecular structure enables molecules to have different molecular packing modes in different aggregation states [16, 24] .…”
Section: Introductionmentioning
confidence: 99%
“…The most common approach to obtaining MSR properties is to construct π-conjugated donor-acceptor (D-π-A) molecular structures with through-bond charge transfer (TBCT) properties. [8,16,[22][23][24][25][26] The π-conjugated molecular structure enables molecules to have different molecular packing modes in different aggregation states. [16,24] Moreover, a variety of stacking modes for the π-conjugated molecules are prepared by varying the excitation light, solvent polarity, [25] solution concentration, external pressure, [8] etc.…”
Section: Introductionmentioning
confidence: 99%
“…The room temperature phosphorescence (RTP) materials are a category of promising luminescent materials with a large Stokes shift, long-lived emission, and other peculiar photophysical properties. [1][2][3][4] Compared with inorganic phosphorescence materials, pure organic RTP materials are superior in organic light-emitting diodes (OLEDs), [5][6] high-sensitive chemical sensing, [7] information encryption, [8][9] high-resolution biological imaging, [10][11][12] data storage [13][14][15] with advantages of low cost, simple preparation process and easy color tunability. [16] The new design ideas for constructing ultralong organic room temperature phosphorescence (UORTP) materials have been attracting much attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Organic room temperature phosphorescence (RTP) materials with a long afterglow property have unique advantages in anticounterfeiting, biological diagnosis and treatment, and optoelectronic devices. Intersystem crossing (ISC) of excitons and stable triplet excitons are prerequisites for organic materials to exhibit phosphorescence. Early organic RTP materials were mainly single-component compounds; the researchers increased the ISC ability of excitons by introducing carbonyl groups or halogen atoms into the molecules or designing donor–acceptor type molecular configurations. , As an emerging technology in recent years, people have found that guest–host doped strategy can cause the doped materials to have RTP activity, which has attracted widespread attention. The host matrix can help the energy transfer of guest excitons, and the rigid structure of the host can effectively limit the motion of the guests, thereby stabilizing the triplet excitons. However, despite the rapid development of doped RTP materials, these systems are basically two-component systems, which are often limited by low performance and limited functionality.…”
mentioning
confidence: 99%